Perancangan Sistem Pakar Untuk Diagnosa Tingkat Stres Belajar Siswa Sma Menggunakan Metode Forward Chaining - Umar, Sanusi San (JUSS (Jurnal Sains dan Sistem Informasi), 2025)
Expert systems are computer-based systems that use knowledge, facts and reasoning techniques to solve problems that can usually be solved by an expert in a particular field. The development of expert systems is actually not to replace the role of humans, but to subsidize human knowledge in the form of expert system-based applications. Expert systems made in this study to find out the symptoms of stress that are often experienced by students. Based on the results of observations made at counseling teachers in several high schools in the city of Banda Aceh-Indonesian, information was obtained that, stress symptoms often experienced by students included environmental factors, friends, mood, and family factors. The purpose of this study is to design expert systems to diagnose stress levels of learning in high school students using the Forward Chaining method. The approach used for designing software uses Prototype models, namely through the activity of gathering information needs from teachers in schools, building prototype models as the initial display that can be seen by the teacher, evaluating prototypes, then creating program coding, testing systems, evaluating systems and using systems that has been built. The results of the study obtained that the design of this expert system can help teachers to diagnose the level of stress experienced by their students and this expert system can be accessed by high school students to help students know the level of stress they experience.